Enhancing gain and bandwidth in a multiband microstrip patch antenna through L-slot and partial ground plane integration - Balamurugan C; Arun Samuel T.S; Merlin Gilbert Raj S; Pricilla Mary S; Sharon Geege A (Scientific Reports)
Abstract A multiband microstrip patch antenna for WiMAX applications is designed, simulated, and fabricated. The proposed antenna achieves multiband operation by introducing slots and slits into the radiating patch element, enabling resonance at multiple desired frequencies. A flame-retardant epoxy material (FR4) with favorable dielectric properties is used as the substrate. This work introduces a low-profile, compact multiband patch antenna that is engineered to resonate precisely at the three standardized WiMAX frequencies (2.4, 3.6, and 5.57 GHz). Although slot- and slit-loaded antennas have been previously investigated, the novelty is in the meticulous geometrical tuning of these features to simultaneously achieve high gain and wide impedance matching at all three bands using a single-layer FR-4 substrate, without the need for metamaterials or multilayer fabrication. The structure that has been proposed offers a cost-effective and practicable solution for the deployment of real-time WiMAX. It achieves a maximal gain of 5.7 dBi, surpassing many of its existing counterparts in terms of efficiency and bandwidth compactness. The maximum realized gain of the antenna reaches 5.7 dBi at 5.57 GHz, demonstrating its effectiveness for high-frequency wireless communication. The fabricated prototype was tested, and the measured results show good agreement with the simulated data across the wide frequency range of 2 GHz to 6 GHz. Additionally, a performance comparison with previously reported multiband microstrip antennas highlights the advantages of the proposed design in terms of gain, bandwidth, and compact structure, making it a promising candidate for WiMAX and other modern wireless applications.